On the influence of nucleation on the toughness of iPP/EPR blends with different rubber molecular architectures (eXPRESS Polymer Letters)
The influence of α-and β-nucleating agents on the fracture performance of two different 32 wt% rubber modified isotactic Polypropylene (iPP) reactor blends is discussed as a function of the phase morphology of the investigated systems. Nucleation for systems with a large inter-particle distance was found to have only a limited impact on the temperature at which the ductile-brittle transition occurs, negative for α-nucleated blends, almost negligible for β-nucleated resins. For blends exhibiting a small inter-particular distance between their ethylene-propylene rubber (EPR) phase, toughness was promoted slightly by α-nucleation and to a large extent by β-nucleation as compared to a non-nucleated reference. These findings raise the importance of mechanistic synergies between the rubbery phase and the matrix to maximize the fracture resistance of blends.